Decree Of The President Of The Arab Republic Of Egypt No. 80 Of The Year 2013 On Amending Certain Provisions Of The Presidential Decree No. 176 Of The Year 2005 On Increasing Pensions As Amended By Decree No. 122/2013 = قرار رئيس جمهورية مصر العربية رقم 80 لسنة 2013 بتعديل بعض أحكام قرار رئيس الجمهورية رقم 176 لسنة 2005 بزيادة المعاشات معدل بالقرار رقم 122 لسنة 2013 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.